2018
DOI: 10.17503/agrivita.v40i0.1650
|View full text |Cite
|
Sign up to set email alerts
|

Development and Survivorship of Scirtothrips dorsalis Hood (Thysanoptera: Thripidae) in Different Growth Stages of Mango and Selected Weeds

Abstract: The research objective was to quantify the development and survivorship rate of S. dorsalis in different phenological stages of mango and selected weeds. The research was conducted in the laboratory of PT. Trigatra Rajasa, Mango plantation in Ketowan, Arjasa, Situbondo, East Java, Indonesia from February to September 2015. The development and survivorship rate were done through observation of life span of S. dorsalis from egg to pupa. Analysis of Variance and Duncan Multiple Range Test (p = 0.05) with 5 replic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Derksen, Mannion, Seal, Osborne, & Martin (2016) revealed that S. dorsalis transfered from main host to the surrounding weed when the population was over. Affandi, dela Rosa Medina, Velasco, Javier, & Depositario (2018) observed that flush growth stage of mango and D. leptophyllus including Ach. indica were given the same range S. dorsalis life cycle from egg to adult i.e.…”
Section: Population Dynamic In High Input Blockmentioning
confidence: 99%
See 1 more Smart Citation
“…Derksen, Mannion, Seal, Osborne, & Martin (2016) revealed that S. dorsalis transfered from main host to the surrounding weed when the population was over. Affandi, dela Rosa Medina, Velasco, Javier, & Depositario (2018) observed that flush growth stage of mango and D. leptophyllus including Ach. indica were given the same range S. dorsalis life cycle from egg to adult i.e.…”
Section: Population Dynamic In High Input Blockmentioning
confidence: 99%
“…Scirtothrips dorsalis is one of the pest which was known to reduce the production and quality of mango (Affandi et al, 2017). The economic lost due to S. dorsalis attack on mango reached 1.040 -1.300 USD/ha (Affandi et al, 2018). Application of pesticide is the most common way to control S. dorsalis.…”
Section: Introductionmentioning
confidence: 99%
“…However, many biotic and abiotic factors limit the normal functioning and growth of mango plants and affect their final yield (Ahmad et al 2019). Among the biotic constraints, weeds, diseases and insect pest are of prime importance (Affandi et al 2017, Shahbaz et al 2017, Malik et al 2018.…”
Section: Introductionmentioning
confidence: 99%